On the language of Giovanni Battista Lalli's "Franceide" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
Giovan Battista Lalli composed several comic works in verse, attributable to the heroic-comic genre despite a far from rigorous adherence to the canons of the genre according to Alessandro Tassoni’s formulation (a trait that, moreover, unites Lalli to other authors of heroic-comic poems). This contribution presents some observations on the style and language of the Franceide, a poem on syphilis published by Lalli in 1629.
Keywords: History of Italian Language; XVII century; Italian literature; Giovan Battista Lalli; Franceide; heroicomic